Current-induced domain wall motion attributed to spin Hall effect and Dzyaloshinsky–Moriya interaction in Pt/GdFeCo (100 nm) magnetic wire. (20th June 2016) - Kurokawa, Yuichiro; Kawamoto, Masaya; Awano, Hiroyuki
Abstract: We investigated the current-induced domain wall motion (CIDWM) in Pt/GdFeCo bilayer wires where the thicknesses of the GdFeCo layer are 110 and 150 nm. We found that the direction of CIDWM in the Pt/GdFeCo wires is the same as the current flow direction. The velocity of the domain wall depends on the in-plane magnetic field. These results indicate that the CIDWM along the current direction in the Pt/GdFeCo wires is probably attributed to the spin Hall effect and Dzyaloshinsky–Moriya interaction. Generally, these effects do not appear in thick magnetic wires because they effectively occur at the interfaces of a heavy metal and magnetic layers. Therefore, these results are interesting phenomena because they probably suggest that the spin Hall effect and Dzyaloshinsky–Moriya interaction in the Pt/GdFeCo wire have an anomalously long-range influence.